2010
DOI: 10.1245/s10434-010-1172-3
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Outcome of Chemotherapy-Induced Amenorrhea in Premenopausal Young Patients with Breast Cancer with Long-Term Follow-up

Abstract: The most important predictors of CIA are age and the addition of tamoxifen to the chemotherapy. CIA is likely to have an influence on DFS and OS in premenopausal patients with breast cancer with a positive hormone receptor, and it might be used as a surrogate marker for effective chemotherapy in these young Asian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 22 publications
1
30
0
2
Order By: Relevance
“…Overall, amenorrhea rates become pronounced in patients' C40 years of age [34] but many studies do not stratify by age. In addition, the very limited data on women under 35 show extremely low rates of CIA (0-10% in most studies) [35]. Although the diagnosis of breast cancer is rare in this age group, definitive data would be extremely useful as these women are most likely to have not completed child-bearing.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, amenorrhea rates become pronounced in patients' C40 years of age [34] but many studies do not stratify by age. In addition, the very limited data on women under 35 show extremely low rates of CIA (0-10% in most studies) [35]. Although the diagnosis of breast cancer is rare in this age group, definitive data would be extremely useful as these women are most likely to have not completed child-bearing.…”
Section: Methodsmentioning
confidence: 99%
“…Still, how tamoxifen influences ovarian toxicity remains unclear. The suggested mechanisms of interference include the alteration of the hypothalamic-ovarian feedback loop regulating estrogen synthesis and higher plasma estradiol levels, due to the selective estrogen receptor modulation induced by tamoxifen [35,70].…”
Section: Endocrine Treatmentmentioning
confidence: 99%
“…Women presenting FSH levels within the normal range may have suffered significant damage to the ovaries. Studies have shown that FSH levels were significantly higher in women presenting amenorrhea after oncological treatment, however the FSH levels were within the normal range in women with diminished ovarian reserve but regular menstrual cycles [61,62]. Women with diminished ovarian reserve have a limited opportunity window to conceive naturally because they present higher risks of ovarian failure and infertility.…”
mentioning
confidence: 99%